Efektivitas Program Literasi Pasar Modal Syariah oleh OJK terhadap Pemahaman Mahasiswa Universitas Al-Amien Prenduan - Hifdani Amal Abdika; Zaid Raya Argantara (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This research aims to analyze the implementation of the Islamic capital market literacy program by the OJK and evaluate its effectiveness in improving the understanding of Al-Amien Prenduan University students. The focus of this research is not only on the level of student understanding, but also on how the literacy program affects students’ perceptions, attitudes, and interest in sharia investment.This study uses a qualitative method with a descriptive approach. Data was collected through semi-structured interviews with students who had participated in the Islamic capital market literacy program. In addition, data was also obtained through observation and documentation as support. The data analysis technique is carried out through the stages of data reduction, data presentation, and conclusion drawn, with the aim of obtaining an in-depth picture of student understanding and the effectiveness of the literacy program implemented.The results of the study show that students have a fairly good understanding of the sharia capital market, including basic concepts, sharia principles, and types of investment instruments such as sharia stocks, sukuk, and sharia mutual funds. The literacy program organized by the OJK has proven to be effective in increasing understanding and changing students’ perception of investment to be more positive and inclusive, as well as increasing interest in investing. However, the effectiveness of the program is still limited to cognitive and affective aspects, and is not fully optimal in encouraging real changes in investment behavio.